Work Fatigue among Women Fish Processors on the South Coast of Jember District, Indonesia - Syamila, Ana Islamiyah; Ma'rufi, Isa (The Indonesian Journal of Occupational Safety and Health, 2024)
Introduction: Occupational Health and Safety (OHS) problems need to be addressed because the cause of the high number of work accidents is work fatigue. One of the factors that causes work fatigue is workload. Coastal women, who are identified as a marginal group with a low level of education, have a large role in fishing households and have a high workload. This research aims to analyze work fatigue based on workload. Methods: This research is an analytical observational study with a cross-sectional design. The respondents involved were fishermen's wives who lived in the research locus (Puger District). The number of respondents in this study was 75 people using proportional stratified random sampling techniques. The quantitative data collected include sociodemographic factors, namely demographic factors (age and body mass index) and work factors (work period, workload, and work climate), as well as work fatigue factors. Data collection was carried out using questionnaires and measurements. The data in this study were analyzed univariately and bivariately using the Spearman rank correlation coefficient test which was presented in table form accompanied by narrative. Results: The results show that 44.0% have a level of heavy work fatigue. The risk factors of age, working time, and workload have a significant relationship with work fatigue at work. Body mass index (BMI) and work climate were not significantly related to work fatigue. Conclusion: The high workload of women fish processors causes a lot of work fatigue, so it requires attention from industry owners to manage working time.